Nutritional status of schoolchildren in Kuantan, Pahang - Mat Ya, Roselawati; Afandi, Aflah; Mohd Abu Bakar, Wan Azdie (2015)
This study aimed to determine the nutritional status among primary schoolchildren in Kuantan, Pahang and to map the distribution using Geographical Information System (GIS). This community based cross sectional study was conducted in Kuantan, Pahang. Stratified random sampling method was used to select schoolchildren from seven subdivision of Kuantan district. A total of 391 schoolchildren age 7 years old were recruited. Data was collected using a questionnaire consisted of questions on socio demographic and anthropometry measurement. Schools’ coordinate were recorded and Geographical Information System (GIS) software was used to map and visualize the distribution of schoolchildren according to nutritional status. Findings showed that 13.8% (n=54) of the children were having overweight and obesity, 10.5% (n=41) stunting and 9.5% cases of underweight (n=37). The mean for BMI-for-age z score (BMIAZ), height-for-age score (HAZ) and weight-for-age z score (WAZ) were 0.07(1.68), -0.64(1.105), and -0.32(1.68) respectively. There were significant difference of BMIAZ and WAZ between urban and rural area (p=0.016) and (p=0.033). There were no significant difference between the three anthropometric measurements with gender, (p=0.947), (p=0.551) and (p=0.613) respectively. There was a significant association between WAZ with income per capita (p=0.014) but there is no association between BMIAZ, HAZ and WAZ with other socio demographic factors including education, occupation and household size. This study shows that the nutritional status among schoolchildren in this area is a major concern. The results warrant the need for further investigation to identify the root causes of childhood obesity in order to develop informed policy, intervention programs and guidelines.